MENELAAH KEMBALI PRINSIP ZAKAT PRODUKTIF (Upaya Mengubah Masyarakat Konsumtif Menuju Masyarakat Produktif) - Abdul Wasik (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2020)
Productive zakat is one of the solutions in improving human resources, not only in terms of welfaring the poor but also professionalizing Amil Zakat (zakat manager). Surely this goal requires other devices to support the creation of human resources improvement. One of the supporting devices is the creation of productive zakat principles. Among the principles of productive zakat that must be prioritized are the following: Principles of Professionalism and Accountability, Principles of Empowerment, Principles of Benefit, Principles of Sustainability, Principles of Jurisprudence. The purpose of the management of productive zakat is to increase public awareness and increase the function and role of religious pranata in an effort to realize the welfare of social justice society, as well as increasing the use and use of zakat and transforming the consumptive society into a productive society.